Cascade Oxidative C−H Annulation of Thiophenes: Heck‐Type Pathway Enables Concise Access to Thienoacenes. (23rd April 2021) - Chen, Xingyu; Yang, Yudong; Han, Weiguo; Huang, Quan; Huang, Zhenmei; You, Jingsong
Abstract: The pursuit of efficient synthetic route to thienoacenes represents an appealing yet challenging task in the fields of both organic synthetic chemistry and organic functional materials. In this work, we disclose a rhodium‐catalyzed cascade C−H annulation of phenacyl phosphoniums with (benzo)thiophenes via a Heck‐type pathway to provide a new class of planar thienoacenes, which involves the formation of three Caryl ‐Caryl bonds and one Caryl −O bond in a single operation. The neutral S, O‐heteroacenes exhibit superior stability and adopt a herringbone‐like packing mode with efficient π–π stacking in the crystals, suggesting their potential in organic semiconducting materials. This work first exemplifies the superiority of cascade oxidative C−H annulation involving a Heck‐type pathway in the development of concise access to heteroacenes. Abstract : A rhodium‐catalyzed cascade oxidative C−H annulation provides a rapid access to a new class of planar thienoacenes with superior stability. Heck‐type pathway is firstly exemplified as a superior process enabling multiple C−H fusions of heteroaromatics for the synthesis of heteroacenes.